PERGESERAN SISTEM PEMBENTUKAN KATA BAHASA INDONESIA: KAJIAN AKRONIM, BLENDING, DAN KLIPING - M. Zaim (Masyarakat Linguistik Indonesia, 2015)
This article aims at describing word formation rules, and word formation shift on acronym, clipping, and blending found in written language of bahasa Indonesia. Data were taken from selected newspaper and magazines published nationally and locally in Indonesia. The findings indicates that there are some shifts in the Indonesian word fomation rules of bahasa Indonesia especially for acronym, blending, and clipping. The shift occurs in the absorption of acronyms, blendings, and clippings of foreign languages. Apart from that, there is a variety of changes to the new forms of acronyms, blendings, and clippings.